2005
DOI: 10.1345/aph.1e484
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Linezolid in Obese Patients with Cellulitis

Abstract: Serum concentrations of oral linezolid in this patient population were diminished compared with those of healthy volunteers, but still provided prolonged serum inhibitory activity against common pathogens associated with skin/soft tissue infections. One treatment concern would be an obese patient receiving oral linezolid who was infected with a less susceptible (MIC > or =4.0 microg/mL) strain of S. aureus. Bactericidal activity was also observed against selective pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 34 publications
2
46
0
2
Order By: Relevance
“…Previously published data have reported lower linezolid concentrations in obese patients (7)(8)(9)(10). One study with seven obese patients receiving 600 mg oral linezolid every 12 h for cellulitis (9) compared a 1-h linezolid concentration of 12.3 g/ml in their patients with previously reported peak concentrations of 16.3 to 24 g/ml in nonobese patients (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published data have reported lower linezolid concentrations in obese patients (7)(8)(9)(10). One study with seven obese patients receiving 600 mg oral linezolid every 12 h for cellulitis (9) compared a 1-h linezolid concentration of 12.3 g/ml in their patients with previously reported peak concentrations of 16.3 to 24 g/ml in nonobese patients (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…There are no weight-based recommendations or guidelines for dosing linezolid in obese patients. However, there is some evidence from case reports and small studies with sparse blood sampling that concentrations may be lower in obese patients, thus requiring dosage increases (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Plates were incubated for 18 to 24 h at 37°C, after which time the zone sizes were measured using a protocol reader (Protocol; Microbiology International, Frederick, MD). Linezolid samples were evaluated using a validated high-performance liquid chromatography (HPLC) assay with standards ranging from 0.5 mg/liter to 30 mg/liter (12,24,35). This assay has a CV of 1.1 to 4.4%.…”
Section: Methodsmentioning
confidence: 99%
“…The study concluded standard dosing in patients weighing up to 150 kg should provide equivalent drug exposure. In contrast, two independent pharmacokinetics studies by Hamilton et al and Stein et al found significant differences in linezolid concentration in obese patients compared to nonobese patients [12,13] . Hamilton et al concluded that the average linezolid concentration was more than 50% lower in the pre-surgery period compared to the post-surgery period in patients with gastric bypass surgery [12] .…”
mentioning
confidence: 82%